(untitled) (Avocetta, 2025)
Falcons display a variety of social behaviours. Species like the lesser kestrel (Falco naumanni) engage in social behaviour during both the breeding and post-breeding periods, forming communal roosts. Other species, such as the common kestrel (Falco tinnunculus), exhibit a more solitary lifestyle, displaying territorial behaviour towards competing breeding pairs during the breeding season and towards other individuals during the non-breeding season. Large aggregations of common kestrels are exceedingly rare, and aggregations of the two kestrel species discussed here have not been described yet. In this study, we present observational data from a mixed communal roost in southern Kosovo. Additionally, this is the first documented observation of a pre-migratory roost of lesser kestrels in Kosovo. We further highlight behavioural differences between the two species and the nature of their interspecific interactions.